The Community Food Environment and Food Insecurity in Sioux Lookout, Ontario: Understanding the Relationships between Food, Health, and Place. Issue 6 (2nd November 2019) - Parker, Barbara; Burnett, Kristin; Hay, Travis; Skinner, Kelly
ABSTRACT: The purpose of this community-based research project was to explore the community food environment and food insecurity in the northern Ontario community of Sioux Lookout. Previous informal conversations with local organizations identified food insecurity as a serious concern with particularly impactful consequences for Indigenous well-being. Community members were invited to a feast at the Friendship Centre where individuals participated in surveys ( N = 76) and talking circles ( N = 100) around the question: "When it comes to food what do you think is the most important issue in Sioux Lookout?" Four related themes emerged including: (1) The Community Food Environment; (2) Indigenous Food Knowledge; (3) Concerns about Health; and (4) Moving Forward. This article considers the community food environment and the relationships between people, food, culture, health, and place.